Recurrent prescription of sleep medication among primary care patients with type 2 diabetes: an observational study of real-world registry data - Eveliina Heikkala; Jari Jokelainen; Ilona Mikkola; Juha Auvinen; Maria Hagnäs (BMC Primary Care, 2023)
Abstract Background Little knowledge exists on the prevalence of recurrent sleep medication prescriptions among primary care patients with type 2 diabetes (T2D). Our aims were to examine the prevalence of recurrent sleep medication prescriptions and to elucidate the most often prescribed sleep medications in a Finnish primary care T2D population. Methods The study examined 4,508 T2D patients who consulted a primary health care center between 2011 and 2019 in Rovaniemi, Finland. All the data were retrieved from patient records, and recurrent sleep medication was defined as two or more prescriptions within the study period. We used the Chi-square and Kruskal–Wallis tests to compare patients who did and did not have recurrent sleep medication prescriptions. Results Altogether 28.1% of the T2D patients had been prescribed recurrent sleep medication. Benzodiazepine-like medication, melatonin, and mirtazapine were most often prescribed (to 56.9%, 44.4%, and 35.8%, respectively). Only 22.0% of the patients with recurrent sleep medication prescriptions had been diagnosed with a sleep disorder. Conclusions Recurrent sleep medication prescriptions are frequent among primary care T2D patients. It seems that sleep disorders are underdiagnosed in relation to this. Primary care clinicians should carefully estimate the need for sleep medication when treating T2D patients’ sleep problems and emphasize the diagnostic patterns of sleep problems.